Construction and validation of a scale of losses experienced in old age (SLO). Issue 11 (2nd November 2021) - Thumala-Dockendorff, Daniela; Assar, Rodrigo; Wenk, Elisabeth; Arnold-Cathalifaud, Marcelo; Villagra, Roque; Lillo, Patricia; Slachevsky, Andrea
ABSTRACT: Individuals tend to accumulate a larger number of losses in old age than in prior stages of life, leading to major consequences for the well-being of older adults. Research has generally focused on a single type of loss, with only a handful of studies exploring the accumulation of losses in old age and examining which and how many losses are experienced, and how intense they are. The lack of instruments that reflect the diversity of the losses that individuals can sustain at this stage of life makes it difficult to accumulate knowledge in this field, since it is not possible to characterize this experience or establish associations with other significant variables. Based on a prior categorization of six types of losses, developed upon the basis of reports by older adults, we sought to construct and validate a Scale of Losses Experienced in Old Age (SLO). This scale underwent semantic validation, followed by content validation. Afterward, for the construct validation process, it was administered to a pilot sample of 249 middle-income community-dwelling older adults. The confirmatory factor analysis yielded adequate values (RMSEA = 0.060, CFI = 0.969, TLI = 0.961, SRMR = 0.075), with internal consistency also being suitable (ordinal alpha = 0.856). These values warrant recommending the use of the SLO, since it offers a view of losses in old age that is both broad and detailed, thus facilitating the production of cumulative and comparable knowledge in the field of psychogerontology while also making it possible to establish interdisciplinary connections.